2009
DOI: 10.1016/j.dyepig.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent bisazomethine dye derived from 3-hydroxyquinoxaline-2-carboxaldehyde and 2,3-diaminomaleonitrile

Abstract: a b s t r a c tA novel bisazomethine Schiff base was synthesised by the condensation of 3-hydroxyquinoxaline-2-carboxaldehyde and 2,3-diaminomaleonitrile. 1 H NMR, 13 C NMR, HPLC and FT-IR studies revealed that the compound exists in two major tautomeric forms. The Schiff base exhibits positive absorption and fluorescent solvatochromism and displays dual fluorescence with large stoke shifts. Cyclic voltammetric analysis of the compound in 1:1 methanol-THF was influenced by scan rate. Thermal analysis of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…(shoulder) and 424 nm. The electronic spectrum of the species corresponding to the major peak is due to the amide form and that corresponding to the minor peak is due to the iminol from [23]. Thus the Schiff base exhibits prototropic tautomerism and exists in the predominant amide form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(shoulder) and 424 nm. The electronic spectrum of the species corresponding to the major peak is due to the amide form and that corresponding to the minor peak is due to the iminol from [23]. Thus the Schiff base exhibits prototropic tautomerism and exists in the predominant amide form.…”
Section: Resultsmentioning
confidence: 99%
“…The highest energy absorption bands in the solution spectra (all solvents) are assigned to p / p* transitions by virtue of their large molar extinction coefficients ( Table 1). The n / p* transitions of the quinoxaline ring appears as a shoulder band around 355 nm [23]. The band centered on 420 nm is due to the n / p* transitions of the azomethine group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maclachlan et al [12] for the �rst time reported the crystal structures of Schiff base derived from DAMN and salicylaldehyde with some metal complexes. A novel bisazomethine Schiff base formed by the condensation of 3-hydroxyquinoxaline-2-carboxaldehyde and 2,3-diaminomaleonitrile has been carried out by Arun et al [13]. e studies revealed that the compound exists in two major tautomeric forms and the Schiff base exhibits positive absorption and �uorescent solvatochromism and displays dual �uorescence with large stoke shi�s.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the Schiff base ligand involved two steps: synthesis of 3‐hydroxyquinoxaline‐2‐carboxaldehyde followed by its condensation with 2‐amino‐5‐chlorobenzophenone. The aldehyde was synthesized by following a procedure reported earlier . The ligand, 3‐{[(2‐benzoyl‐4‐chlorophenyl)imino]methyl}quinoxalin‐2(1 H )‐one ( L ), was synthesized by adopting the following procedure.…”
Section: Methodsmentioning
confidence: 99%